GEOLOGY OF CIBEUREUM AND SURROUNDING AREAS, CIBEUREUM DISTRICT, KUNINGAN REGENCY, WEST JAVA PROVINCE - Ahmadjayadi, Tigfhar; Pratiwi, Santi Dwi; Iskandarsyah, Teuku Yan Waliana Muda (Fakultas Teknik Geologi Universitas Padjadjaran, 2023)
This study compiled a comprehensive geological map of Cibeureum and its surrounding areas in Cibeureum District, Kuningan Regency, West Java, using primary data and systematic geological methods, including field observations, data sampling, and laboratory analysis. Geographically, the area is located at 108o 42' 33.75